A Case for Using Ability-Based Emotional Intelligence Measures in the Selection of Trainee Psychologists. Issue 1 (January 2016) - Omoregbee, Itohan; Morrison, Ben W.; Morrison, Natalie M.V.
Abstract: At present, selection into Masters and Doctorate level Clinical Psychology programs in many countries largely relies upon undergraduate grades (i.e., Grade Point Average; GPA) and the honors year thesis. The use of objective, non-cognitive measures of ability are virtually non-existent. One measure seemingly relevant to the field of clinical psychology is the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT), an ability-based measure of emotional intelligence (EI). EI, the ability to identify and regulate one's own (and others') emotions, may act as a worthwhile predictor of performance within domains requiring advanced communication and empathy skills, such as clinical psychology. Testing a sample of first year Masters of Clinical Psychology students ( n = 9), this study investigated the relationship between EI as measured by the MSCEIT, performance in clinical tasks (simulated Cognitive Behavioral assessment and Cognitive Therapy (CT) competencies), and GPA. Despite a modest sample size, results indicated a significant correlation between EI and results from the clinical tasks, but there was no significant relationship between assessment performance and GPA. Implications to higher education selection and the clinical psychology profession are discussed.